The gender wage gap and sample selection via risk attitudes. Issue 2 (2nd May 2017) - Jung, SeEun
Abstract : Purpose: The purpose of this paper is to consider a new way of estimating the gender wage gap by introducing individual risk attitudes that is applied to representative Korean data. Design/methodology/approach: The selection bias via risk attitudes results in the overestimation of this wage gap. Women are more risk averse and hence prefer not to be active in the labour market or, if they are active, prefer to work in the public sector, where wages are generally lower than in the private sector. This paper explains the reduced gender wage gap by developing an appropriate sample-selection model, with wage decompositions corrected for selection. Findings: Self-selection based on risk attitudes is shown to partly explain the gap that is popularly perceived as reflecting gender discrimination. Originality/value: It is the first attempt to explain the gender wage gap by looking at the individual risk preference through work status selection.